THE EFFECT OF INFLATION, EXCHANGE RATES, INTEREST RATES AND MONEY SUPPLY ON THE JAKARTA ISLAMIC INDEX (JII) STOCK PRICE INDEX FOR THE PERIOD 2018-2022 - Isnaini, Alfath; Nasir, Muhammad; Hilmi, Hilmi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The capital market is an important element in the economy in Indonesia. Measuring the performance of shares marketed on the stock exchange is used an index, namely the Stock price index (IHS).This study aims to determine the effect of Inflation, Exchange Rate, Interest Rate and Money Supply on the Stock Price Index listed on the Jakarta Islamic Index (JII) for the period 2018-2022. The analysis method used is the panel data regression method with the selected model being the Common Effect Model (CEM). The population in this study were all companies listed on the Jakarta Islamic Index (JII) for the 2018-2022 period, totaling 30 companies. Determination of the number of samples was carried out using Purposive Sampling technique and determined as many as 9 Company samples. The t test results show that partially Inflation has a negative and significant effect on the Stock Price Index, Exchange Rate and Interest Rate have a positive and significant effect on the stock price index. While the money supply does not have a significant effect on the Stock Price Index. The results of the F test show that simultaneously Inflation, Exchange Rate, Interest Rate and Money Supply have a significant effect on the stock price index in the Jakarta Islamic Index (JII) for the period 2018-2022.